Self-Similar Flow Behind a Spherical Radiation-Driven Shock Wave in Magnetogasdynamics - Singh, J. B.; Ram, R. K. (Defence Science Journal, 2014)
Adiabatic and isothermal self-similar flows behind a radiation-driven shock wave in the presence of magnetic field have been investigated by using the generalised method of Laumbach and Probstein for magnetogasdynamics. The density and magnetic field distributions of the gas ahead of the shock have beenassumed to be constant.